If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4w + 2x = 7y Solving 4w + 2x = 7y Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-2x' to each side of the equation. 4w + 2x + -2x = -2x + 7y Combine like terms: 2x + -2x = 0 4w + 0 = -2x + 7y 4w = -2x + 7y Divide each side by '4'. w = -0.5x + 1.75y Simplifying w = -0.5x + 1.75y
| (3x-3)(x^2-x-8)= | | 10x^3=80 | | 5x+2y-z=-29 | | 5+15x=2+16x | | 2x-3/5=x+3/4 | | 17=2(2m+9) | | -4y+12=-2(4y+6) | | 6=3+5d-10 | | s^2-12s+32=0 | | (3x+1)+(3x+1)+(x+1)+(x+1)=24 | | 20=2a+3a | | 6f=4 | | 5x-9=7x-7 | | 124+x=x+76 | | 5x-6=45x+2 | | x-2/5=1/2 | | 5(x-2)+3(x-1)=3 | | -2=-(m-8) | | 4(w-5)-7W=-29 | | x+0.5+3x-2=3x+1.5 | | R-3.14=3.14 | | 6x+4y=170 | | 5(4-x)=10x | | 8b=73 | | p+1.6+(-0.4)=-12 | | 5x-10+3x-3=3 | | 2y^3-y=4 | | 3x+x+(x+7)=32 | | 2(9u-4)=4(u+5) | | 7b/2-10=-3 | | 1n-9n=1 | | 7t+6-2(5+3t/2)=5t-11 |